Ensemble modeling of the coupled carbon cycle-climate system ... - Frölicher, Thomas L. (:unas, 2009)
The overarching theme of this thesis is the impact of anthropogenic carbon emissions on the coupled carbon cycle-climate system. This topic is connected to three specific research questions: (i) the role of internal unforced variability, natural forced variability by explosive volcanism and anthropogenic changes, (ii) the understanding of the long-term consequences of anthropogenic carbon and greenhouse gas emissions, and (iii) the impact of ongoing oceanic carbon uptake and climate change on ocean acidification and dissolved oxygen (O2) depletion. Anthropogenic emissions of carbon dioxide (CO2) and other forcing agents force the atmospheric composition, Earth’s climate, and the chemical state of the ocean towards conditions that have probably not occurred over the past 20 million years (Blackford and Gilbert, 2007) and at a speed that is unprecedented at least during the last 22’000 years (Joos and Spahni, 2008). Today’s atmospheric CO2 concentration of 386 ppm is above the natural range (172 to 300 ppm) of ...